Incidence trends and survival prediction of hepatoblastoma in children: a population-based study - Feng, Jincheng; Polychronidis, Georgios; Heger, Ulrike; Frongia, Giovanni; Mehrabi, Arianeb; Hoffmann, Katrin (Cancer communications, 2019)
Hepatoblastoma is a rare disease that nevertheless accounts for the majority of liver malignancies in children. Due to limited epidemiological data, therapy for hepatoblastoma tends to be individualized. This study aimed to evaluate incidence trends of hepatoblastoma and to develop a nomogram to predict the survival of children with newly diagnosed hepatoblastoma on a population-based level.
Gesehen am 19.11.2019